Drying Characteristics of Coarse Low-Rank-Coal Particles in a Fixed-Bed Dryer - Pusat, Saban; Erdem, Hasan Huseyin (TAYLOR & FRANCIS INC, 2017)
In this study, a Turkish lignite (the Konya-Ilgin lignite) was used to study its drying characteristics in a fixed-bed dryer. The drying experiments were conducted with coarse lignite particles for utilization in the heating sector. In this study, the effects of the drying-air temperature and velocity were investigated. The particle sizes inside the bed were kept constant in the experiments, which was different from the previous works cited in the literature. The results showed that the drying-air temperature and velocity significantly influence the drying process. The drying time was reduced by increasing the air temperature and velocity. Additionally, drying of Konya-Ilgin lignite did not show an explicit constant-drying-rate stage. It showed the falling-drying-rate stage only despite containing more than 50% moisture by weight. This situation is different from most of the studies in the coal-drying literature.
Keywords: Lignite; coal; low-rank coal; drying characteristics; coarse particle; fixed bed; LIGNITE PARTICLES; SUPERHEATED STEAM; TEMPERATURE; ENERGY; TECHNOLOGIES; FLUIDIZATION; SIMULATION; KINETICS; MOISTURE; INDUSTRY; Energy & Fuels; Mining & Mineral Processing